INSTITUTIONAL AND ORGANIZATIONAL MECHANISMS FOR MANAGING MODERN RISKS IN THE CIVIL PROTECTION SYSTEM (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the institutional and organizational mechanisms for managing modern risks in the civil protection system. The increasing frequency of climate change impacts, technogenic accidents, epidemiological threats, and natural disasters necessitates the improvement of civil protection systems worldwide. The study examines the concept and classification of modern risks, as well as the interaction of management entities within the framework of civil protection. Particular attention is paid to the effectiveness of institutional structures and the role of organizational management mechanisms in risk reduction. Based on international experience, the importance of an integrated approach to modern risk management is substantiated, and scientific and practical recommendations for the development of the civil protection system are proposed.